Peran hukum perlindungan konsumen dalam melindungi hak-hak dan kewajiban konsumen - Nurhaliza, Devina Binti (Maliki Interdisciplinary Journal, 2024)
Consumer rights and authorities are important things that must be regulated, therefore consumer rights and obligations have been regulated in Law Number 8 of 1999 concerning Consumer Protection. In this article, the aim is that consumer protection rights and obligations exist to resolve a problem if a trial occurs. In this article, we use the method of dependence on regulations and literature study. Discussed in this article is the understanding of consumer protection law, the legal basis used and also the rights and obligations of consumers in consumer protection law. These rights and obligations are contained in articles 4 and article 5. In this case, consumer protection law plays a role in resolving settlements that occur between business actors and consumers.